Folic acid fortification of flour : determination of the level that gives rise to unmetabolised folic acid in serum - Sweeney, Mary Rose (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2001)
To prevent neural tube defects the Food and Drug Administration (FDA) implemented mandatory folic acid fortification o f all flour milled in the USA at a level 140μg/100g. The Centers for Disease Control (CDC) have proposed that this level be increased to 350μg and even 700μg/100g. However previous research carried out in this laboratory has shown that doses of folic acid as low as 266μg administered acutely saturates the normal intestinal absorption mechanisms and results in unmetabolised folic acid in serum post-prandially. This may present a problem in the early diagnosis of pernicious anaemia. In addition the efficacy of anti-folate agents used in the treatment of various conditions such as epilepsy, rheumatoid arthritis and inflammatory intestinal disorders may be affected by the presence of unmetabolised folic acid in the circulation. Finally toxic effects as a result of large doses of folic acid in the circulation such as teratogenic defects and certain cancers have not been investigated.
Keywords: Clinical Medicine, M.D.; Ph.D. Trinity College Dublin